The Effectiveness of Fraction Boards in Helping Concrete-Thinking Students Internalize the Concepts of Fractions - Muhamad Saleh; Bansu Irianto Ansari; Murni; Manovri Yeni; Abubakar; Anwar; Muhammad Isa; Roslina (Revija za Elementarno Izobraževanje)
The final year of research aims to investigate the effectiveness of chocolate-shaped fraction boards in helping students internalize the concepts of fractions and correct procedures for performing fraction operations (addition and subtraction). The research design is descriptive qualitative. Thirty-five fourth graders at SD Negeri 8 Banda Aceh were involved as research participants. The data were collected through observations during the learning sessions. The results showed that the chocolate-shaped fraction boards are effective in helping the students perform fraction operations accurately, such as identifying equivalent fractions, equalizing the denominators of two simple fractions, and adding and subtracting simple fractions.